2021
DOI: 10.14520/adyusbd.932914
|View full text |Cite
|
Sign up to set email alerts
|

Epi̇stemoloji̇k İnancin Eleşti̇rel Düşünme Eği̇li̇mi̇ Ve Akademi̇k Özyeterli̇k İle İli̇şki̇si̇ni̇n İncelenmesi̇

Abstract: The aim of this study is to examine the structural relationships between secondary school students' epistemological beliefs, their critical thinking dispositions and their academic self-efficacy. The research was conducted according to the correlational research method, and structural equation modeling was used in the analysis of the data. The data of the study were obtained from 678 secondary school students studying in Afyonkarahisar. Epistemological Belief Scale, Critical Thinking Disposition Scale and Acad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…They concluded that teacher training institutions should increase their efforts in this direction. Kandemir and Eğmir (2021) stated that epistemological beliefs significantly predict academic self-efficacy and that critical-thinking disposition has a full mediation effect in this relationship.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They concluded that teacher training institutions should increase their efforts in this direction. Kandemir and Eğmir (2021) stated that epistemological beliefs significantly predict academic self-efficacy and that critical-thinking disposition has a full mediation effect in this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Scholars have observed that epistemological belief is a type of belief that affects motivation and academic achievement during learning (Aşut & Köksal, 2015) and individuals with developed epistemological beliefs have characteristics such as being active, independent, determined, flexible and broad-minded (Jehng et al, 1993). In this direction, authors have stated that academic self-efficacy is another issue that is thought to be effective on preservice teachers' epistemological beliefs in their educational processes (Kandemir & Eğmir, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation